2013
DOI: 10.1016/j.dynatmoce.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Upper-bound general circulation of coupled ocean–atmosphere: Part 1. Atmosphere

Abstract: We consider the general atmospheric circulation within the deductive framework of our climate theory. The preceding three parts of this theory have reduced the troposphere to the tropical and polar air masses and determined their temperature and the surface latitude of their dividing boundary, which provide the prior thermal constraint for the present dynamical derivation. Drawing upon its similar material conservation as the thermal property, the (columnar) potential vorticity (PV) is assumed homogenized as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…This paper completes our five-part climate theory aiming to derive the generic climate state forced only by the solar insolation [6][7][8][9]. Subjected to the bulk thermal properties previously determined, we derive the upper-bound GOC above the main thermocline when PV is homogenized, the latter being supported on theoretical, computational, and observational grounds.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…This paper completes our five-part climate theory aiming to derive the generic climate state forced only by the solar insolation [6][7][8][9]. Subjected to the bulk thermal properties previously determined, we derive the upper-bound GOC above the main thermocline when PV is homogenized, the latter being supported on theoretical, computational, and observational grounds.…”
Section: Discussionmentioning
confidence: 68%
“…In a companion paper on the general atmosphere circulation [9], we have shown that its upper bound may replicate the observed prevailing wind as well. Together with the present paper, we posit that PV homogenization provides a unifying dynamical principle for the general planetary circulations, which may be interpreted as the maximum macroscopic motion extractable by microscopic stirring-within the confines of thermal differentiation.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In a companion paper [9], we have applied the same principles to derive the upperbound general atmospheric circulation (GAC), which is seen to resemble the prevailing wind, forsaking therefore previous discordant explanations of the easterly trade and the polar jet stream. In the present paper, we shall show that the upper-bound GOC may replicate the observed GOC as well, including a western-intensified subtropical gyre and a counter-rotating tropical gyre feeding the equatorial undercurrent (EUC).…”
Section: Introductionmentioning
confidence: 99%